Application of Quality Management System in Tourism Sector in Kosovo - Lleshi, Samir; Syka, Xhenet (European Journal of Economics and Business Studies, 2016)
Tourism is one of the most complex activities of today’s modern society. In developed countries and in some other countries in transition, it presents a significant product of export and employment generator. The increase of the quality of service and application of the quality management system in tourism industry is undoubtedly a challenge that we are all interested to deal with. Quality Management of Services is directly connected with training and qualification of human resources involved in this sector. Tourism sector in recent years, although, it was a priority for each government, we can freely say, it has increased in spontaneous way. More tourists don’t mean more progress in development, or generating of incomes for Kosovars. The type of tourism that one country is commited to develop is mainly determined from the contribution for enriching of its inhabitants. Emphasizing of natural and cultural tourism in Kosovo is mainly focused on benefiting from local communities, which, unfortunately, are currently facing the limited economic situation. Positive benefiting from a successful tourism sector strategy directly contributes to increase of employment, additional benefitting for economy, improved infrastructure and increase of tax revenue which directly has an impact in improvement toward health care, education, and other social development.